2020
DOI: 10.1021/acsami.0c08605
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Ultralow Activation Energies for Lithium Transport in Garnet Electrolytes

Abstract: Garnet-type structured lithium ion conducting ceramics represent a promising alternative to liquidbased electrolytes for all-solid-state batteries. However, their performance is limited by their polycrystalline nature and the inherent inhomogeneous current distribution due to the different ion dynamics at grains, grain boundaries and interfaces. In this study we use a combination of electrochemical impedance spectroscopy, distribution of relaxation times analysis and solid state nuclear magnetic resonance (NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…Subsequent improvement of conduction properties in novel oxide materials following their original report in the literature is often observed. For instance, benchmark Li-rich garnets oxides were originally reported to have ionic conductivities on the order of 10 −6 S cm −1 with activation energies in the 0.4-0.5 eV range, comparable with our novel Li 1.5 La 1.5 TeO 6 double perovskite, and improvements in the last decade have seen these values rise to above 10 −3 S cm −1 with activation energies below 0.2 eV [65][66][67] . The low local Li + activation energy below 0.2 eV and similar Li + diffusion coefficient obtained by µ + SR here for the Li 1.5 La 1.5 TeO 6 material is comparable to that of the LLZO benchmark garnet electrolyte probed by the same technique, where again pellet microstructure greatly impacts the macroscopic transport properties 21 .…”
Section: Resultssupporting
confidence: 74%
“…Subsequent improvement of conduction properties in novel oxide materials following their original report in the literature is often observed. For instance, benchmark Li-rich garnets oxides were originally reported to have ionic conductivities on the order of 10 −6 S cm −1 with activation energies in the 0.4-0.5 eV range, comparable with our novel Li 1.5 La 1.5 TeO 6 double perovskite, and improvements in the last decade have seen these values rise to above 10 −3 S cm −1 with activation energies below 0.2 eV [65][66][67] . The low local Li + activation energy below 0.2 eV and similar Li + diffusion coefficient obtained by µ + SR here for the Li 1.5 La 1.5 TeO 6 material is comparable to that of the LLZO benchmark garnet electrolyte probed by the same technique, where again pellet microstructure greatly impacts the macroscopic transport properties 21 .…”
Section: Resultssupporting
confidence: 74%
“…[30][31][32][33] The ionic transport was reported to be limited by the grain boundaries, which are heavily affected by the segregation of dopants and Li. 34 Mechanical polishing, carbon annealing or acid treatment were reported to remove this unwanted surface layer. 35,36 Metal or non-metal coatings on garnet pellets, which consequently enables lithium alloying, have also been used to minimise the interfacial resistance between lithium metal and garnet, and to reduce the dendrite growth.…”
Section: Introductionmentioning
confidence: 99%
“…For the LLZO family of materials it has been demonstrated that the intrinsic charge transfer resistance across the Li/LLZO interface is very small once contaminant layers have been removed. 17,19,20,21 Analogously, in the Na ''alumina system, the removal of hydroxyl and carbon contaminants through heat treatment in an inert atmosphere was found to lead to very small (<10 cm 2 ) interfacial Ω resistances with Na metal. 12 Improvement of the wetting between alkali metals and SSE surfaces has been achieved in several studies through the addition of a thin, metallic interlayer phase.…”
Section: Introductionmentioning
confidence: 93%